Stability Analysis of Patients with Various Neurological and Musculoskeletal Disorders based on Linear and Nonlinear Approaches - Mina Mirahmadi; Mohammad Taghi Karimi; Javid Mostamand (Vesnu Publications, 2014)
Abstract Introduction: Stability is the ability of subjects to keep their upright posture, which is enhanced by combination strategies of various musculoskeletal systems. Various methods have been used to evaluate the abilities of subjects during standing, including linear and nonlinear methods. It is not clear that which one of these two methods has more ability to represent stability of subjects with various neurological and musculoskeletal disorders. Therefore, the aim of this study was to investigate the stability of the subjects with various neurological and musculoskeletal disorders using linear and nonlinear methods. Materials and Methods: Four groups of subjects including, normal subjects and subjects with three different disorders of flatfoot, Parkinson`s Disease (PD), and Perthes were recruited in this study.  A Kistler force plate was used to evaluate the stability of the subjects. The difference between the linear (Center of Pressure Excursion, Velocity and Path Length) and nonlinear (Approximate Entropy = ApEn) parameters was evaluated by two sample t test. Results: The mean value of COP velocity of flatfoot and perthes subjects were 1621/5±405/6 and 878/4±195 mm/min in the medio lateral direction, respectively (P < 0/05). The mean value of ApEn in the anteroposterior direction was 0/94±0/16 in flatfoot subjects and 0/99±0/21 in those with perthes. However, it was 0/45±0/06 in the subjects with PD. The difference between normal subjects and all other groups of participants was significant (P < 0/05). Conclusion: It seems that nonlinear method is more sensitive to represent the difference between stability of subjects with different neurological and musculoskeletal disorders. However when linear approach is selected for data analysis it is suggested to use a group of parameters instead of only one parameter. Depending on the kind of diseases, increasing and decreasing the value of Approximate Entropy represent the instability situations. Keywords: Stability, linear analysis, nonlinear analysis, Parkinson`s Disease, Perthes, flat foot